Marital Relationship : Wife Beating Behavior in a Province of Central Southern Thailand - Muangchana, Charung (Journal of Health Science of Thailand, 2018)
Wife beating behavior not only reflexes marital relationship, but also causes bodily and psychiatric injuries of wives and other family members, including youth. The youth perceives wife beating or physical violence as a way of conflict solving. An analytical descriptive study was conducted to determine prevalence and characteristic of wife beating behavior as well as association between the behavior and socioeconomic factors. Two-stage cluster sampling was applied to randomly selected 30 villages and then 12 women met study criteria were randomly selected from village lists of married women at reproductive ages (MWRA). In all, 360 women not older than 44 years, married and still living as a couple, and lived outside metropolitan area in the selected province of Central Southern Thailand were interviewed about the most recent wife beating behavior by well trained health care workers, during August - September 1997. It was found that about one out of four women or 24.4 percent (95%CI 19.6%-29.6%) had the experience of being beaten by their husbands at least once. Wife beating behavior was found in all husband occupations, but merchants (35.0%) and temporary employees (34.0%) had the highest rate (p-value 0.02). Husbands who ever assaulted others had beaten their wives 2.03 times (95%CI 1.20, 3.45) higher than those who never did. Most (92.1%) of the beating behaviors were slapping, hitting, and kicking. More than half (64.8%) caused no injuries, while 28.4 percent were contusion or swelling. Only 5.7 percent of the assaulted saught care from health facilities. Events that triggered the behavior were general daily life conflicts (44.4%), while common stimulated conditions were drunken husband (23.9%) and husband behaviors such as loitering, not-responsible, and unemployed (20.5%) and family financial problem (12.5%). More than half (62.5%) of wives who were beaten did not fight back their husbands, but 17.1 percent did. Variables not associated with the prevalence were years of marriage, educational level, wife occupation, income and number of children. In conclusion, wife beating behavior is common, but mostly hidden. It should be concerned in the society and prevention and control measures should be applied to prevent body injuries, psychiatric problems and other violence in society.